HOUSEHOLD-SCALE REARING OF CANTANG GROUPER LARVAE (EPINEPHELUS FUSCOGUTTATUS × EPINEPHELUS LANCEOLATUS) AT UD. ARIF HATCHERY, GEROKGAK DISTRICT, BULELENG REGENCY, BALI - Raufurrahman, Muhamad; Anna fauziah; Nazran, Nazran (Jurnal Perikanan Unram, 2025)
The maintenance of cantang grouper larvae on a household scale faces challenges in maintaining water quality, feeding, and disease control. This study aims to analyze maintenance techniques to improve larval survival. The method used is descriptive with observation, interviews, and literature studies. The research was conducted at UD. Arif Hatchery, Bali, with the main parameters observed including temperature, salinity, pH, nitrite and nitrate levels, Survival Rate, and the effectiveness of natural and artificial feed. The results showed that the optimal water quality for the maintenance of grouper larvae was 27–30°C, salinity 30–33 ppt, pH 7.5–8.5, and nitrite levels <0.01 mg/L and nitrates <2 mg/L. Gradual feeding from rotifers, nauplius artemia, to artificial feed was able to increase  the larval survival rate. Water management with flow-through systems and regular flushing also plays an important role in the success of maintenance. From this study, it can be concluded that the application of good maintenance techniques, including water quality control, feeding strategies, and disease management, greatly determines the success of the production of cantang grouper fish fry on a household scale